Effect of surfactant on Pseudomonas aeruginosa colonization of polymer microparticles and flat films. Issue 28 (24th April 2018) - Hüsler, Amanda; Haas, Simon; Parry, Luke; Romero, Manuel; Nisisako, Takasi; Williams, Paul; Wildman, Ricky D.; Alexander, Morgan R.
Abstract : The attachment of Pseudomonas aeruginosa on microfluidic produced particles was shown to reduce as a function of PVA concentration retained at the surface, enabling novel structure–function relationships of biomaterial architecture. Abstract : Micro- and nanoparticles are of great interest because of their potential for trafficking into the body for applications such as low-fouling coatings on medical devices, drug delivery in pharmaceutics and cell carriers in regenerative medicine strategies. Particle production often relies on the use of surfactants to promote stable droplet formation. However, the presence of residual surfactant has been shown to complicate the surface chemistry and resultant properties. When forming particles from polymerizable monomer droplets, these polymeric surfactant chains can become physically entangled in the particle surface. Due to the key role of the outermost layers of the surface in biomaterial interactions, the surface chemistry and its influence on cells needs to be characterized. This is the first study to assess surfactant retention on microfluidic produced particles and its effect on bacterial attachment; surfactant contaminated microparticles are compared with flat films which are surfactant-free. Polymeric microparticles with an average diameter of 76 ± 1.7 μm were produced by using a T-junction microfluidic system to form monomer droplets which were subsequently photopolymerized. Acrylate based monomer solutions were found to require 2 wt% PVA to stabilize droplet formation. ToF-SIMS was employed to assess the surface chemistry revealing the presence of PVA in a discontinuous layer on the surface of microparticles which was reduced but not removed by solvent washing. The effect of PVA on bacterial ( Pseudomonas aeruginosa ) attachment was quantified and showed reduction as a function of the amount of PVA retained at the surface. The insights gained in this study help define the structure–function relationships of the particulate biomaterial architecture, supporting materials design with biofilm control.